Students' Reliance on Artificial Intelligence in Completing Islamic Religious Education Assignments - Tamroini, Irfan Malik; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to synthesize the patterns of use, levels of reliance, ethical issues, and pedagogical implications of student reliance on AI in completing Islamic Religious Education (PAI) assignments, and to formulate practical implications for curriculum development, pedagogy, and educational policy in Islamic education in the digital era. This study uses the Systematic Literature Review (SLR) method, analyzing 37 empirical and conceptual articles published in 2021-2026. Articles were selected from a collection discussing AI in education, with a focus on the Islamic context. The synthesis process was conducted thematically to identify patterns of use, levels of reliance, ethical issues, and pedagogical implications. Two usage patterns were found: AI as a technical tool and as a source of religious content. The level of reliance varied from critical-instrumental to excessive. Ethical issues included violations of academic integrity, erosion of scholarly authority, threats to spiritual development, as well as algorithmic bias and data privacy. Pedagogical implications emphasized assessment transformation, the integration of critical AI literacy based on Islamic values, and strengthening the teacher's role as a moral guide. This study provides the first systematic map of AI reliance dynamics in PAI, where technical, cognitive, and spiritual dimensions intersect. The findings establish an evidence base for creating Islamic ethical guidelines, designing AI-resistant assessments, and strengthening the teacher's role as a moral guide and knowledge curator. It proposes integrating principles like ḥifẓ al-‘aql (intellect preservation), al-amanah al ‘ilmiyyah (knowledge trust), and maṣlaḥah (public benefit) as an essential normative framework to balance technological innovation with educational integrity.